2006
DOI: 10.1038/sj.npp.1301049
|View full text |Cite
|
Sign up to set email alerts
|

The G72/G30 Gene Complex and Cognitive Abnormalities in Schizophrenia

Abstract: A recently discovered gene complex, G72/G30 (hereafter G72, but now termed DAOA), was found to be associated with schizophrenia and with bipolar disorder, possibly because of an indirect effect on NMDA neurotransmission. In principle, if G72 increases risk for psychosis by this mechanism, it might impact with greater penetrance those cortically based cognitive and neurophysiological functions associated with NMDA signaling. We performed two independent family-based association studies (one sample contained mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 41 publications
5
91
2
1
Order By: Relevance
“…Several studies were excluded because of sample duplication with another study (Yue et al, 2006), lack of sufficient data even after requesting informative data from the authors (Fallin et al, 2005;Goldberg et al, 2006;Hall et al, 2004;Nicodemus et al, 2007). M12, M15, M23 and M24 were excluded for BP because they were analyzed in only one or two studies (Schulze et al, 2005).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies were excluded because of sample duplication with another study (Yue et al, 2006), lack of sufficient data even after requesting informative data from the authors (Fallin et al, 2005;Goldberg et al, 2006;Hall et al, 2004;Nicodemus et al, 2007). M12, M15, M23 and M24 were excluded for BP because they were analyzed in only one or two studies (Schulze et al, 2005).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…An association has been reported in multiple independent studies (Addington et al, 2004;Chen et al, 2004;Fallin et al, 2005;Hall et al, 2004;Hong et al, 2006;Korostishevsky et al, 2004;Korostishevsky et al, 2006;Ma et al, 2006;Schulze et al, 2005;Schumacher et al, 2004;Wang et al, 2004;Williams et al, 2006;Yue et al, 2006;Yue et al, 2007;Zou et al, 2005). However, several studies did not find association with traditional BP or SCZ phenotype (Bakker et al, 2007;Goldberg et al, 2006;Liu et al, 2006;Mulle et al, 2005;Vilella et al, 2007;Wood et al, 2006). In addition, an obvious inconsistency of allelic association(s) has been observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goldberg et al (2006) demonstrated a significant effect of several SNPs on cognitive measures, which are putatively dependent on NMDA signaling in a cohort of 600 subjects, including patients with schizophrenia, their unaffected siblings, and healthy controls. Further, these associations were also related to neurophysiological response parameters during those tasks, as measured by functional magnetic resonance imaging (fMRI).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the association of the G72/G30 locus with schizophrenia and bipolar disorder has been reported in several studies. 22,36 Other genes and polymorphisms studied in schizophrenia include a brain-derived neurotrophic factor (BDNF) prodomain polymorphism, 2,41,72 Catechol-Omethyl-transferase (COMT), 42,71,75 gamma aminobutyric acid (GABA), 38,55,59,112 histidine triad nucleotide-binding protein (HINT1) and cytosolic malate dehydrogenase (MDH1). 3,16,109 Some researchers have presented data derived from multimodal imaging or combined data from both imaging and other modalities, including genomic imaging).…”
Section: Introductionmentioning
confidence: 99%